Calculating Standard Reduction Potentials of [4Fe-4S] Proteins - Perrin, Bradley Scott (2012)
The oxidation-reduction potentials of electron transfer proteins determine the driving forces for their electron transfer reactions. While the type of redox site determines the intrinsic energy required to add or remove an electron, the electrostatic interaction energy between the redox site and its surrounding environment can greatly shift the redox potentials. Here, a method for calculating the reduction potential versus the standard hydrogen electrode, E°, of a metalloprotein using a combination of density functional theory and continuum electrostatics is presented. This work focuses on the methodology for the continuum electrostatics calculations, including various factors that may affect the accuracy. The calculations are demonstrated using crystal structures of six homologous HiPIPs, which give E° that are in excellent agreement with experimental results.